2020
DOI: 10.1002/jso.26187
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory preoperative COVID‐19 testing for cancer patients—Is it justified?

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 has caused substantial disruptions in routine clinical care. Emerging data show that surgery in coronavirus disease (COVID)-positive cases can be associated with worsening of clinical outcomes and increased postoperative mortality. Hence, preoperative COVID-19 testing for all patients before elective surgery was implemented in our institution. Materials and Methods: Two hundred and sixty-two asymptomatic cancer patients were preoperatively tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 15 publications
4
27
0
2
Order By: Relevance
“…Interestingly, a careful preoperative screening methodology in elective surgical oncology patients resulted in a low COVID-19 infection in our series (2.1%, n = 2). Some other authors have justified our strategy having similar results ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, a careful preoperative screening methodology in elective surgical oncology patients resulted in a low COVID-19 infection in our series (2.1%, n = 2). Some other authors have justified our strategy having similar results ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 70%
“…Importantly, none of the patients in our study developed any signs or symptoms suggestive of COVID-19 requiring testing during post-operative period. This was also the case in study reported by Nekkanti et al where none of the patients developed any signs of COVID-19 infection [4].…”
Section: Discussionsupporting
confidence: 81%
“…In this study, the authors concluded that with pre-operative screening of patients, head and neck cancer surgery can be performed safely during the pandemic [6]. A study conducted by Nekkanti et al at Tata Memorial Hospital; Mumbai also suggested that pre-operative testing has a beneficial role in giving good post-operative outcomes [4]. There was also a strong recommendation for doing the same by a recent consensus guideline for head and neck cancer management [2].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations